1999
DOI: 10.1063/1.479594
|View full text |Cite
|
Sign up to set email alerts
|

Electron spin resonance and theoretical studies of the 14N⋅⋅⋅⋅14N and 15N⋅⋅⋅⋅15N spin-pair radicals in neon matrices: The effects of mixing among the 1Σg+, 3Σu+, 5Σg+, and 7Σu+ electronic states

Abstract: The first experimental and theoretical study of the N⋅⋅⋅⋅N spin-pair radical is reported. Its high-resolution ESR (electron spin resonance) spectrum has been observed in neon matrices and interpreted on the basis of weakly interacting atoms using a model recently developed for the H⋅⋅⋅⋅H spin-pair. To fully interpret the N⋅⋅⋅⋅N radical results it was necessary to include electronic state mixing effects among all possible spin states, namely the 1Σg+, 3Σu+, 5Σg+, and 7Σu+ states. Several different trapping site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 20 publications
2
8
0
Order By: Relevance
“…Small interactions between the host and the trapped species can result in small changes in the spectroscopic properties observed, in this case, the D -value, and as the matrix is believed to be crystalline, these interactions are specific to a particular site . The absorption near 1730 G corresponds to two spin-coupled N atoms, N···N, which has been described by Knight et al The position of the three peaks is consistent with the spectrum generated by a 4 ∑ – radical with | D | between 5000 and 10 000 MHz. A quartet radical with this | D | value produces a set of perpendicular ( xy 1 ) lines around 1900 G, a set of off-angle lines around 5000 G and another set of perpendicular ( xy 3 ) lines around 6000 G, which are all shown in Figure .…”
Section: Resultssupporting
confidence: 83%
“…Small interactions between the host and the trapped species can result in small changes in the spectroscopic properties observed, in this case, the D -value, and as the matrix is believed to be crystalline, these interactions are specific to a particular site . The absorption near 1730 G corresponds to two spin-coupled N atoms, N···N, which has been described by Knight et al The position of the three peaks is consistent with the spectrum generated by a 4 ∑ – radical with | D | between 5000 and 10 000 MHz. A quartet radical with this | D | value produces a set of perpendicular ( xy 1 ) lines around 1900 G, a set of off-angle lines around 5000 G and another set of perpendicular ( xy 3 ) lines around 6000 G, which are all shown in Figure .…”
Section: Resultssupporting
confidence: 83%
“…Each neon atom is surrounded by 12 neon atoms. The distance between two neon atoms is 3.16 Å . In our calculations, only one shell was employed and the center neon atom was replaced with NH 4 and OH 3 molecules.…”
Section: Methods Of Calculationmentioning
confidence: 99%
“…ESR assesses the interaction of the intrinsic electronic spin with the magnetic nuclei. In recent years, there has been a number of ESR investigations (both theoretical and experimental) for gaining knowledge about electronic structures, spin density distributions, and hyperfine splittings for various radical/ion systems. In this paper, we reexamine the electronic structures of NH 4 , OH 3 , and FH 2 at the MP2 level with a large basis set augmented with Rydberg-type diffuse orbitals. The potential energy surfaces are calculated, and the relative stabilities of NH 4 , OH 3 , FH 2 , and their isotopic counterparts are discussed.…”
Section: Introductionmentioning
confidence: 99%
“…In a pair of papers, Knight et al, have demonstrated how eqn (2.1) with the Heisenberg interaction term can be used to fit the ESR spectrum of matrix separated H atoms in 2 S states and for matrix separated N atoms in 4 S states. 3,4 As both experiments involved atoms with zero orbital angular momentum (S states), additional complexity from rotational degeneracy was avoided and the separate radical D KK values were zero. The separation distances were large enough however that the D KL values (which decrease like the inverse cube of the separation distance) were larger than J (which decreases exponentially).…”
Section: Macroscopic and Microscopic Hamiltoniansmentioning
confidence: 99%